Resource potential of some species of the genus Miscanthus Anderss. under conditions of continental climate of West Siberian forest-steppe - O. V. Dorogina; O. Yu. Vasilyeva; N. S. Nuzhdina; L. V. Buglova; Yu. A. Gismatulina; E. V. Zhmud; G. A. Zueva; O. V. Kominа; Е. A. Tsybchenko (Вавиловский журнал генетики и селекции)
In the meantime, search for environmentally friendly renewable energy sources alternative to fossil fuel has been driven by energy security challenges including limited availability of fuel and energy price fluctuations. Therefore herbal perennial grasses with their rapid growth and prominent biomass yield increasingly make it a favorite choice as a valuable agricultural crop usable for cellulosic ethanol production. As an example, the genus Miscanthus Anderss. (silvergrass) comprises ca. 14–20 species including M. sacchariflorus (Maxim.) Hack., M. sinensis Anderss., M. purpurascens Anderss, and M. × giganteus, which appear to be an almost inexhaustible source of sustainable raw material, and several Miscanthus species were investigated as a potential biofuel energy crop with commercially viable way of its producing. Introduction and investigation of Miscanthus species were initiated in the Central Siberian Botanical Garden of the Siberian Branch of the Russian Academy of Sciences (CSBG SB RAS, Novosibirsk, Russia) based on the grass and ornamental plant collection in the late 1990s. The paper objective is studying the biological traits of three Miscanthus species introduced into the CSBG SB RAS, selection and genetic identification of cultivars and varieties as the most perspective agricultural crop. To evaluate the potential crop yield and selection prospects of Miscanthus species being competitive as a valuable biofuel energy crop, the authors have estimated seasonal rhythms of model species development in the continental climate conditions of West Siberia. The article characterizes different Miscanthus varieties obtained either by the ex situ or in situ methods; presents the biochemical analysis of plant material and molecular identification of three Miscanthus species introduced into the CSBG SB RAS. The seasonal development analysis of three selected varieties of Miscanthus (M. sacchariflorus, M. sinensis, and M. purpurascens) proved the hydrometeorological conditions to be advantageous for prominent biomass yield, e. g. contributory to use Miscanthus in West Siberia as an easy to grow cellulose-rich grass. Molecular markers applicable in DNA-identification and genetic passportization of Miscanthus varieties have been established, which are perspective as such an economically available plant material as alternative non-woody source of cellulose.